Performance test and process parameter optimization of 9FF type square bale straw crusher - Zhang, Jie; Feng, Bin; Guo, Lei; Kong, Lingzhuo; Zhao, Chao; Yu, Xiuzhen; Luo, Wenjie; Kan, Za (International Journal of Agricultural and Biological Engineering, 2021)
In order to solve the problem of low productivity, unqualified segment length and high energy consumption during the process of crushing square bale straw caused by improper operation parameters, a 9FF square bale straw crusher was developed. In this study, by taking maize straw as the test material, the feeding speed, spindle speed of the crushing device and the state of the crushing device were taken as influence factors, and standard straw length rate, productivity per net working hour (hereinafter referred to as NWH) and energy consumption per ton of product as test indicators, the influence of the factors on the indicators were studied, and tests were carried out on the process of square bale straw crushing. By adopting the single factor test on the effect of the feeding speed, the spindle speed of the crushing device and the state of the crushing device on the test indicators, the suitable range of each factor was determined, respectively. Using the orthogonal test method, range method, variance method and comprehensive balance method, the experiment analyzed the significance of the influence of the three factors on various indicators and the order of priority. The test results showed that: the feeding speed was 5 m/min, spindle speed was 3000 r/min, and the state of the crushing device was a mixing cutter hammer, which was the best parameter combination (A1B1C1) for the processing technology of the square bale forage crusher. The standard straw length rate was 93.7%, and the productivity per NWH was 2.80 t/h, with energy consumption per ton of 4.72 kW•h/t, in which the standard straw length rate and productivity per NWH reached optimal values, and the energy consumption per ton of product was slightly higher than the optimal value in the experiment. The research results can provide a reference for the optimal design of the special crusher for square bale straw. Keywords: square bale, straw crusher, crushing, working parameter optimization, performance test DOI: 10.25165/j.ijabe.20211403.5970 Citation: Zhang J, Feng B, Guo L, Kong L Z, Zhao C, Yu X Z, et al. Performance test and process parameter optimization of 9FF type square bale straw crusher. Int J Agric & Biol Eng, 2021; 14(3): 232–240.